Construction of Exosomes that Overexpress CD47 and Evaluation of Their Immune Escape - Ben, Xin-Yu; Wang, Ya-Ru; Zheng, Hui-Hui; Li, De-Xian; Ren, Rui; Ni, Pan-Li; Zhang, Hai-Ying; Feng, Ren-Jun; Li, Yun-Qing; Li, Qi-Fu; Yi, Xi-Nan (Frontiers in Bioengineering and Biotechnology, 2022)
Our general purpose was to provide a theoretical and practical foundation for the use of exosomes (EXOs) that have high levels of CD47 as stable and efficient drug carriers. Thus, we prepared EXOs from adipose tissue-derived mesenchymal stromal cells (ADMSCs) that had high levels of CD47 (EXOsCD47) and control EXOs (without CD47), and then compared their immune escape in vivo and their resistance to phagocytosis in vitro. Nanoflow cytometry was used to determine the CD47 level in these EXOs, and the amount of EXOsCD47 that remained in rat plasma at 3 h after intraperitoneal injection. Phagocytosis of the EXOs was also determined using in vitro rat macrophage bone marrow (RMA-BM) experiments. Our in vitro results showed that macrophages ingested significantly more control EXOs than EXOsCD47 (P < 0.01), with confirmation by ultra-high-definition laser confocal microscopy. Consistently, our in vivo results showed that rats had 1.377-fold better retention of EXOsCD47 than control EXOs (P < 0.01). These results confirmed that these engineered EXOsCD47 had improved immune escape. Our results therefore verified that EXOsCD47 had increased immune evasion relative to control EXOs, and have potential for use as drug carriers.